Voice Assessment Before and After Phonetic Voice and Pronunciation Exercises - Varošanec - Škarić, Gordana (2003)
The research objective has been to confirm the efficiency of phonetic voice and pronunciation exercises. The results of listeners' assessment have then been compared to the objective parameters f0, shimmer and jitter, as well as to the spectra energy on the basis of LTASS. The dissimilarity index (SDDD) has been calculated to compare the spectra before and after the exercises. Voices that have improved the most have had higher SDDD values. There has also been more relative energy in the area of voluminosity and sonority. Phonetic exercises have proved efficient for improving the timbre of the voice, making it more consistent, better set and for sharpening the speech.
Projekt MZOS
ENG